1983
DOI: 10.1113/jphysiol.1983.sp014711
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline hyperpolarizes cells of the canine coronary sinus by increasing their permeability to potassium ions.

Abstract: SUMMARY1. The mechanism ofthe noradrenaline-induced hyperpolarization was investigated in small strips of coronary sinus tissue mounted in a fast-flow system.2. The recorded hyperpolarization was negligibly small in response to 10 nmnoradrenaline but was maximal at 10/SM (average amplitude 23 mV, in 4 mM-K solution). The hyperpolarization was unaffected by 1 /SM-phentolamine but was abolished by 10 /uM-propranolol and so is presumably mediated via fl-adrenoceptors.3. The noradrenaline-induced hyperpolarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 35 publications
5
23
0
Order By: Relevance
“…The hyperpolarization induced by j3-agonists was attributed to an enhancement of Na-K pump activity (TRAUTWEIN and SCHMIDT, 1960;AKASU et al, 1977). But, BOYDEN et al (1983) noted direct action of j3-agonists on permeability of potassium in the canine coronary sinus, and GADSBY (1983) reported similar findings in the case of Purkinje fibers. j3-Agonists are also considered to enhance the outward current (lout) through an increase in the slow inward current (Isi) in view of the Ca activated outward current (SIEGELBAUM et a1.,1977;SIEGELBAUM and TSIEN, 1980;GoTo et al, 1982GoTo et al, , 1983URATA and GoTo, 1982).…”
supporting
confidence: 53%
See 1 more Smart Citation
“…The hyperpolarization induced by j3-agonists was attributed to an enhancement of Na-K pump activity (TRAUTWEIN and SCHMIDT, 1960;AKASU et al, 1977). But, BOYDEN et al (1983) noted direct action of j3-agonists on permeability of potassium in the canine coronary sinus, and GADSBY (1983) reported similar findings in the case of Purkinje fibers. j3-Agonists are also considered to enhance the outward current (lout) through an increase in the slow inward current (Isi) in view of the Ca activated outward current (SIEGELBAUM et a1.,1977;SIEGELBAUM and TSIEN, 1980;GoTo et al, 1982GoTo et al, , 1983URATA and GoTo, 1982).…”
supporting
confidence: 53%
“…From these results it was proposed that /3-agonists directly increase the background 'k, currents. Recently, BOYDEN et al (1983) andGADSBY (1983) noted that hyperpolarization was a direct action induced by ,9-agonists, something which has usually been attributed to the enhancement of the Na pump activity. They observed that R-agonists could induce a hyperpolarization in the canine coronary sinus and Purkinje fibers even after the inhibition of Na pump by acetylstrophanthidin and/ or K-free solution and that the reversal potentials of I V curves determined with and without the drugs vary with [K]0 as does Ek, and concluded that j3-agonists increased the K permeability directly, as did the cholinergic agonists.…”
Section: Js-actions On Cardiac Membrane Currents 525mentioning
confidence: 99%
“…This was verified in some experiments by application of ACh in the presence of low [Na]0, which resulted in a further hyperpolarization of a few millivolts (see Fig. 5B of Boyden et al 1983). It seems likely that at least some of the remaining deviation of the membrane potential from EK in low Na solution can be attributed to inward current carried by the remaining extracellular Na ions.…”
Section: The Effects Of [Ca]mentioning
confidence: 98%
“…sudden application of acetylcholine, sudden increase in [K]0, or sudden decrease in [Na]0, the resting potential attains within a few seconds a level that indicates that EK and [K]i are high. In fact, the 176 P. A. BOYDEN, P. F. CRANEFIELD, D. C. GADSBY AND A. L. WIT membrane potentials attained during those interventions indicate that [K]i is normally about 155 mm in coronary sinus cells (see also Boyden et al 1983), a value similar to that reported for Purkinje fibres (Carmeliet, 1961;Miura, Rosen & Hoffman, 1977;Gadsby & Cranefield, 1977;Wier, 1978;Sheu, Korth, Lathrop & Fozzard, 1980;Wiederholt, Daniesevskis, Hansen, Lickey & Platsch, 1980), for myocardial cells of ventricles (Lee & Fozzard, 1975;Cohen & Fozzard, 1978;Browning & Strauss, 1981;Baumgarten, Cohen & McDonald, 1981) and atria (Singer, Baumgarten & Miller, 1980;Browning, Kerr & Strauss, 1980) and for cells of the sino-atrial node (Browning et al 1980) and atrio-ventricular node (Baumgarten, 1982). Since the resting potential normally lies so far from EK, the cell membrane clearly cannot be exclusively permeable to K ions.…”
Section: The Effects Of [Ca]mentioning
confidence: 99%
See 1 more Smart Citation